Type 2 Diabetes: What Went Wrong with Insulin? - Sorouri, Kimia; Liang, Ellen (The Meducator, 2014)
Type 2 diabetes mellitus, or non-insulin dependent diabetes mellitus (NIDDM), is a pathological condition characterized by an inadequate response to insulin, a hormone responsible for regulating blood glucose levels. NIDDM comprises of 90-95% of all cases of diabetes.1 Normally, insulin is released by pancreatic beta cells into the bloodstream, acting on receptors found in tissues such as skeletal muscle and the liver.2 The binding of insulin to insulin receptors stimulates glucose uptake into cells and the storage of glucose as glycogen (glycogenesis).3 Evidence suggests that genetic mutations may increase susceptibility to NIDDM. Specifically, a reduction of insulin receptor gene expression may be partly responsible for insulin resistance in NIDDM.4 While molecular pathways are not very well understood, evidence suggests high blood fatty acid levels may inhibit insulin receptor substrates (IRS) in the insulin-signalling cascade.4 The isoforms of the glucose transporters (GLUTs) primarily involved in diabetes are GLUT2 and GLUT4.5 There is currently limited data linking specific genes to diabetic pathology, warranting for genome-wide analyses.6 Despite an increasing prevalence of diabetes, there is encouraging evidence supporting the ability of exercise to reduce insulin resistance.7